Evolutionary mechanisms of the strong winds associated with an intense cold wave event and their effects on the wind power production - Ma, Hui; Li, Guoqing; Zeng, Chuikuan; Wang, Fei; Jin, Shuanglong; Fu, Shenming (Frontiers in Earth Science, 2023)
The cold wave events (CWEs) often cause major economic losses and serious casualties in the cold seasons, which makes them one of the most important types of disastrous weathers. Thus far, related studies mainly focused on the disasters that were due to the abrupt dropping of the surface temperature, whereas, the strong winds associated with the CWEs were much less discussed. Based on an intense CWE occurred in late December 2020, we investigated the variation mechanisms of its associated strong winds in terms of kinetic energy (KE) budget, and evaluated the CWE’s effects on the wind power production by conducting quantitative comparisons with the mean state. It was found that, the CWE occurred under favorable background conditions, which were characterized by a southward moving transversal trough and a southeastward-moving shortwave trough in the middle troposphere. The surface high ridge that formed around the Lake Baikal and the cold front around the southern periphery of the ridge served as the key factors that governed the CWE’s evolution. The positive work done on the horizontal wind by the pressure-gradient-force that linked a lower tropospheric high-pressure ridge inland and a low-pressure trough offshore, and the downward momentum transportation due to the descending motions behind the cold front dominated the enhancement/sustainment of the CWE-associated strong winds. The CWE contributed to the wind power production through (i) increasing the wind power density (by ~1.05 times on average), and (ii) improving the availability of the wind for generating power, as it reduced the percentage of zero wind power generation (by ~6.4%), while keeping the high-wind-velocity cut-out percentage almost unchanged.